Strategi Pengembangan Iklim Investasi di Provinsi Bengkulu - handoko hadiyanto (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2022)
The objectives of this research is to know the growth of investment in Bengkulu Province and to know the strategy of Increasing Investment in Bengkulu Province. The type of this research was qualitative descriptive research. The type of data the in this study were secondary data and primary data. The method of analysis was SWOT analysis. The results show that the analysis that must be done used the Weakness and Opportunity (WO) Strategy which is in the third quadrant, namely: Minimizing weaknesses to take advantage of opportunities, to conduct appropriate analysis in minimizing weaknesses and taking advantage of opportunities. The strategy that must be done carried out promotional activities that describe the state of the existing resources in Bengkulu Province so that it can attract investors who enter through the DPM-PTSP to invest in Bengkulu Province through the Regional Investment Promotion Program with activities carried out by the Bengkulu Provincial government, namely through the media. Existing media, both printed and electronic, that describe the advantages of investing in Bengkulu Province, provide legal certainty for investors to invest in Bengkulu Province by providing certain products (licensing) so that investors feel comfortable investing and making deregulation to further simplify the process cooperation and coordination with the technical team in providing recommendations for the issuance of permits and non-permits through the Bengkulu Province so that the process of issuing permits and non-permits was not complicate and takes a long time and was expensive to obtain. the community, the business world and investors feel that they were not harmed, the presence of unscrupulous employees commits extortion and the absence of handling complaints/complaints makes it difficult to establish good cooperation between the Government and the business world so that the Government through legal certainty must be more assertive in dealing and taking action against extortionists and existing complaints.